2001
DOI: 10.1021/ja002359t
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Isomerization of 1,1,2,2-Tetrafluoroethane (FC-134) to 1,1,1,2-Tetrafluoroethane (FC-134a) in the Presence of Hydrogen

Abstract: The mechanism of the high-temperature, gas-phase isomerization of 1,1,2,2-tetrafluoroethane (FC-134) to 1,1,1,2-tetrafluoroethane (FC-134a) in the presence of H 2 has been explored both experimentally and computationally. Studies of the impact of temperature, H 2 /FC-134 ratio, and contact time on conversion and yield, as well as a study of deuterium incorporation when D 2 was used in place of H 2 , led to the conclusion that a free radical chain mechanism involving rearrangement of CHF 2 CF 2 ‚ to CF 3 CHF ‚ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…This lack of observation of CHF 2 CHF 2 in the CHF 3 pyrolyses is undoubtedly the result of its H 2 -promoted isomerization to CF 3 CH 2 F at these high temperatures. This isomerization, which does not occur thermally in the absence of H 2 , is the subject of the accompanying paper …”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…This lack of observation of CHF 2 CHF 2 in the CHF 3 pyrolyses is undoubtedly the result of its H 2 -promoted isomerization to CF 3 CH 2 F at these high temperatures. This isomerization, which does not occur thermally in the absence of H 2 , is the subject of the accompanying paper …”
Section: Resultsmentioning
confidence: 88%
“…Reports of fluorine atom shifts in carbon radical systems are rare, but such rearrangements are apparently feasible. In the accompanying paper, UB3LYP/6-311+G(2df,2p)//UB3LYP/6-31G(d) calculations provided an estimated barrier ( E ⧧ ) of 29.2 kcal/mol for this rearrangement . On the basis of these calculations, we believe that the unimolecular 1,2-fluorine atom shift of CHF 2 CF 2 · should be competitive with its second, bimolecular H atom abstraction.…”
Section: Resultsmentioning
confidence: 88%
“…It was also noted by Dolbier that the presence of H 2 in the pyrolytic mixture can isomerize 134 to 134a. 601 An alternative strategy proposed by Shields (ICI) prescribes subjecting the 134/134a mixture to a commercially available zeolite (AW-500, for example) at between 200 and 400 °C, though this method is only particularly suitable to reduce the 134 concentration from around 10 000 ppm to <20 ppm. 602 Rao and Subramanian (Du Pont) used their cubic CrF 3 catalyst to effect the disproportionation of a mixture of 124/ 124a (98.5/1.4) to 123 and 125.…”
Section: Kellner Et Al (Du Pontmentioning
confidence: 99%
“…The advantage of this invention in practice is that crude 114 / 114a can be dehydrohalogenated to 134 / 134a and that this mixture can then be isomerized to enrich the 134a fraction. It was also noted by Dolbier that the presence of H 2 in the pyrolytic mixture can isomerize 134 to 134a . An alternative strategy proposed by Shields (ICI) prescribes subjecting the 134 / 134a mixture to a commercially available zeolite (AW-500, for example) at between 200 and 400 °C, though this method is only particularly suitable to reduce the 134 concentration from around 10 000 ppm to <20 ppm …”
Section: Hydrofluorocarbons (Hfcs3rd Generation)mentioning
confidence: 99%
“…However, experimental studies of the pyrolysis of CHF 2 -CHF 2 found that the major products were CF 3 CH 2 F (HFC 134a) and C 2 HF 3 under condition of low conversion (2-3%) at 973 K 34. This indicates that if C 2 HF 3 is formed via R14-R17, even larger quantities of CHF 2 -CHF 2 and HFC 134 should be observed.…”
mentioning
confidence: 99%